2017
DOI: 10.21037/jtd.2017.08.25
|View full text |Cite
|
Sign up to set email alerts
|

Protecting lungs during spontaneous breathing: what can we do?

Abstract: door of optimizing ventilator settings and modes to reduce P-SILI remains open. Back to a physiology standpoint, seeking for a ventilatory strategy to minimize P-SILI with preserved spontaneous effort should not and will not stop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…The mean age of our cohort was 63 + 11 yrs with 65% patients being males (Table 1). The duration for the development of barotrauma was 18.5 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days from symptom onset and 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days from hospital admission. Interestingly, despite a high incidence of barotrauma, we did not observe CT-based evidence of emphysema, cysts, or bullae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of our cohort was 63 + 11 yrs with 65% patients being males (Table 1). The duration for the development of barotrauma was 18.5 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days from symptom onset and 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days from hospital admission. Interestingly, despite a high incidence of barotrauma, we did not observe CT-based evidence of emphysema, cysts, or bullae.…”
Section: Resultsmentioning
confidence: 99%
“…5,16,22 Another concerning factor is patient self-inflicted lung injury (P-SILI), which can induce lung injury as a consequence of intense inspiratory efforts. 23,24 The idea has been backed-up by animal models that showed that high tidal volume generated by negative pressure ventilation resulted in pulmonary edema, in a manner similar to positive pressure ventilation. 25 In patients with ARDS and acute hypoxemic respiratory failure, respiratory drive is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shortage of ICU beds during the pandemic, 35 a relatively high number of patients were treated with non-invasive respiratory support for many days even when their clinical status would have required intubation and invasive mechanical ventilation, which may have led to P-SILI. In COVID-19, four potential mechanisms of P-SILI may be suggested: 1) increased lung stress/strain, 36 , 37 , 38 , 39 2) inhomogeneous distribution of ventilation, 4 40 3 ) changes in lung perfusion, 16 23 and 4) patient-ventilator asynchronies during non-invasive positive pressure ventilation (NPPV). 41 42 Increased lung stress/strain …”
Section: Mechanisms Of P-silimentioning
confidence: 99%
“…Although Δ P as a risk factor for VILI has been exclusively studied in patients under controlled mechanical ventilation, the potentially harmful effects of high Δ P are probably present in any mode of ventilation. Recently, the concept of self-inflicted lung injury has been introduced, referring to patients in assisted ventilation [911]. As the beneficial effects of spontaneous breathing during mechanical ventilation are well established, it becomes increasingly important to identify patients at risk of self-inflicted lung injury during assisted ventilation [911].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the concept of self-inflicted lung injury has been introduced, referring to patients in assisted ventilation [911]. As the beneficial effects of spontaneous breathing during mechanical ventilation are well established, it becomes increasingly important to identify patients at risk of self-inflicted lung injury during assisted ventilation [911]. To identify patients at risk and prevent self-inflicted lung injury, monitoring of Δ P during assisted ventilation might be helpful.…”
Section: Introductionmentioning
confidence: 99%